Validation of ACC/AHA and ESC Sudden Cardiac Death Risk Guidelines in Diverse Hypertrophic Cardiomyopathy Cohort: Stratification HCM Study - Murillo Oliveira Antunes; Fabio Fernandes; Edmundo Arteaga-Fernandez; Félix José Alvarez Ramires; Vinicius Machado Correia; Juliano Novaes Cardoso; Cristhian Espinoza Romero; Henrique Martins Sousa; Marília Taily Soliani; Matheus Ramos Ramos Dal Piaz; Anna Danielle Rodrigues Gandarella; Ruiza Gonçalves Rocha Teixeira; et al. (Global Heart)
Background: Sudden cardiac death (SCD) is a major concern in patients with hypertrophic cardiomyopathy (HCM). The American College of Cardiology/American Heart Association (ACC/AHA) and the European Society of Cardiology (ESC) have different guidelines for SCD risk stratification. Their comparative performance in diverse populations remains uncertain. Objective: Evaluate the performance of the 2020 ACC/AHA and 2014 ESC guidelines for SCD stratification in a Brazilian cohort with HCM. Methods: This retrospective cohort study included patients diagnosed with HCM who were followed in a dedicated clinic at a tertiary hospital in Brazil. The primary outcome was SCD, aborted cardiac arrest due to ventricular fibrillation (VF), sustained ventricular tachycardia (SVT), episode of VF or SVT, or appropriate ICD therapy. Risk prediction models were assessed using the C-index. Results: A total of 187 patients were included, with a mean follow-up of 8.3 years. The 2020 ACC/AHA guidelines classified 106 (56%) patients as high-risk for SCD, while the 2014 ESC guidelines identified 54 (29%). The primary outcome occurred in 12% of the high-risk group identified by the ACC/AHA guidelines and 13% of the high-risk group identified by the ESC guidelines. Both guidelines showed low discriminatory power for SCD risk in this Brazilian cohort, with AUC values of 0.634 and 0.581 for the ACC/AHA and ESC guidelines, respectively. Conclusions: The 2020 ACC/AHA and 2014 ESC guidelines have limitations in predicting SCD events and defining ICD indications in Brazilian HCM patients. Further studies are needed to refine risk stratification and optimize SCD prevention in this population.